Assessing the Impact of Work-Life Balance on Employee Job Satisfaction (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This paper present the effect of work life balance on employee job satisfaction, an important determinant of organizational performance and employee turnover. Work-life balance is therefore one of the biggest factors that determine job satisfaction due to the pressure that is placed on employees in the modern world to perform their work as well as attend to their family needs. Employees are satisfied with their jobs when organizations recognize and support work-life balance practices like flexible working hours, remote work, and wellness programs. This means that workers who are able to balance their work and family responsibilities have reduced stress levels, better mental health and increased job satisfaction. In addition, a healthy work-life balance lowers the cases of burnout, turnover, and absenteeism and increases the productivity of the employees. This abstract underlines the problem of the lack of attention to the policies that should promote the employees’ happiness in order to increase job satisfaction and ultimately organisational performance. In light of the growing understanding of companies about the importance of WLB this study also highlights the role of WLB in establishing healthy, motivated and satisfied workforce that is instrumental in long term success. From the analysis of these dynamics, this paper aims at contributing to the understanding of how work-life balance promotion can result in increased job satisfaction and organisational prosperity.